Vitamin B12 analogues from gut microbes and diet differentially impact commensal propionate producers of the human gut - Palni Kundra; Anna Greppi; Monica Duppenthaler; Serafina Plüss; Benoit Pugin; Christophe Lacroix; Annelies Geirnaert (Frontiers in Nutrition, 2024)
To produce the health-associated metabolite propionate, gut microbes require vitamin B12 as a cofactor to convert succinate to propionate. B12 is sourced in the human gut from the unabsorbed dietary fraction and in situ microbial production. However, experimental data for B12 production by gut microbes is scarce, especially on their produced B12-analogues. Further, the promotion of propionate production by microbially-produced and dietary B12 is not yet fully understood. Here, we demonstrated B12 production in 6 out of 8 in silico predicted B12-producing bacteria from the human gut. Next, we showed in vitro that B12 produced by Blautia hydrogenotrophica, Marvinbryantia formatexigens, and Blautia producta promoted succinate to propionate conversion of two prevalent B12-auxotrophic gut bacteria, Akkermansia muciniphila and Bacteroides thetaiotaomicron. Finally, we examined the propiogenic effect of commercially available B12-analogues present in the human diet (cyano-B12, adenosyl-B12 and hydroxy-B12) at two doses. The low dose resulted in partial conversion of succinate to propionate for A. muciniphila when grown with adenosyl-B12 (14.6 ± 2.4 mM succinate and 18.7 ± 0.6 mM propionate) and hydroxy-B12 (13.0 ± 1.1 mM and 21.9 ± 1.2 mM), in comparison to cyano-B12 (0.7 ± 0.1 mM and 34.1 ± 0.1 mM). Higher doses of adenosyl-B12 and hydroxy-B12 resulted in significantly more conversion of succinate to propionate in both propionate-producing species, compared to the low dose. B12 analogues have different potential to impact the propionate metabolism of prevalent propionate producers in the gut. These results could contribute to strategies for managing gut disorders associated with decreased propionate production.